Friction spot joining of aluminum alloy 2024-t3 and carbon-fiber-reinforced polyphenylene sulfide composite laminate with additional pps film interlayer - André, Natália Manente (2015)
Friction Spot Joining (FSpJ) is a prize-winning joining technique for hybrid metal-polymer composite structures. This master thesis was devised to investigate the feasibility of FSpJ of metal-composite structures with additional film interlayer. Friction spot joints of aluminum alloy 2024-T3 and carbon-fiberreinforced polyphenylene sulfide laminate composite with additional PPS film interlayer were successfully produced. The highest peak temperature achieved during the joining process was 417°C. DSC analysis demonstrated that the degree of crystallinity decreased for the composite (from 22% to 12%) and increased for the PPS film (from 7% to 27%) after joining. TGA analysis indicated that no extensive thermo-mechanical degradation induced by the joining process occurred. The main bonding mechanisms of FSp joint were identified as macro- and micro-mechanical interlocking, as well as adhesion forces. The process-related microstructural effects were evaluated and correlated to the local mechanical performance of the joining parts through micro and nanohardness. Further, mechanical grinding, sandblasting and plasma activation surface pre-treatments were performed on the composite part to enhance the adhesion between the joining parts. The generated surface features due to the surface pre-treatments were correlated to the mechanical performance of the joints. Sandblasted specimens showed the best mechanical performance among the surface pre-treatments used in this work. The lap shear strength of joints with interlayer (2703 ± 114 N up to 3069 ± 166 N) was up to 55% higher than the corresponding joints without film. The fatigue life of the joints with interlayer was 4 times longer in comparison with those without interlayer; superior fatigue strength was also observed. The durability of the joints was evaluated through hydrothermal accelerated aging; the maximum reduction in initial strength was 12.4% for 28 days of aging. Finally, the failure mechanisms of the joints were discussed, demonstrating a mixture of adhesivecohesive failure mode.